Empirical Evidence of the Impact of Islamic Financial Inclusion on Human Welfare of Maqashid Sharia Perspective in Indonesia - Rani Puspitaningrum (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose – The study aims to determine the effect of Islamic financial inclusion using 3 (three) dimensions, namely accessibility, availability, and use (usage of banking services) of Islamic banking in Indonesia on the concept of welfare which includes 5 (five) elements: protection (hifz) of religion (din), mind ('aql), soul (nafs), offspring (nasl), and property (mal).Methodology - The Islamic financial inclusion components are represented by several variables: the total number of third-party funds and financing, the total number of deposit accounts, and Automated Teller Machines (ATM) of Islamic banking. Meanwhile, the Islamic Human Development Index (I-HDI) is a suggested variable that represents welfare in the perspective of maqashid sharia. The research data used is annual data from 2010-2019 and then analyzed by multiple linear regression method. Findings - The result shows that Islamic financial inclusion has a significant effect on people's welfare in Indonesia. Variable availability (availability) and the use of Islamic banking services (usage of banking services) have a real influence, but not so on the variable accessibility (accessibility). The increase in Islamic financial services indicated by the increase in third-party funds and financing in Islamic banking will also improve human welfare.Research Implication - The increase of ATMs (Automated Teller Machines) numbers reduces human welfare in Indonesia.Keywords: Islamic financial inclusion, Islamic Human Development Index (I-HDI), material welfare index (MWI), non-material welfare index (NWI), maqashid sharia.